The Impact of Minimum Wages on Employment in a Low-Income Country : A Quasi-natural Experiment in Indonesia - Alatas, Vivi (2012)
The extensive literature on the employment impact of minimum wages has focused heavily on industrialized nations and very little on the developing world, despite the importance of minimum wages in many low-income countries. One such country, Indonesia, was the setting for an unusual quasi-natural experiment: not only did minimum wages in Indonesia increase sharply between 1990 and 1996, but the resultant increment in average wages varied markedly across different areas in Greater Jakarta. The authors use household-level labor market data to determine the extent of compliance with the legislation, then estimate the employment impact in the clothing, textiles, footwear, and leather industries based on a census of all large and medium-sized establishments. The evidence suggests that there was no negative employment impact for large establishments, either foreign or domestic, but that workers in smaller, domestic establishments may have suffered job losses as a result of minimum wage increases.